OSL Dating of a Woodland Period Occupation at the Hare Hammock Ring and Mound Complex, Bay County, Florida - Hodson, Alex (My University, 2015)
This study used OSL dating to examine the chronological relationship between two adjacent archaeological sites at the Hare Hammock complex in northwest Florida. High-resolution vertical sampling was performed at 10cm intervals in profiles, one corresponding to a Swift Creek burial mound, and the other to a Weeden Island ring midden. This was done in order to determine the timing of occupations at the sites and look for patterns in radiation dosimetry. The Swift Creek mound was found to have a mean OSL age of 1835 +/- 68 years, consistent with archaeological expectations of the site and the accepted range of Swift Creek culture. The subsequent Weeden Island occupation was also found to have OSL ages within expectations, with a mean age of 1049 +/- 43 years that overlies a single age of 1511 +/- 372 years, corresponding to the Late and Early Weeden Island periods, respectively. The general coherence with radiocarbon dates and ceramic chronologies affirms the veracity of these OSL ages, which were obtained using a very recently developed dosimetric technique that applies Al2O3:C cylinders as in-situ dosimeters. These dosimeters indicated that the sediments at Hare Hammock contain significant heterogeneity in beta dose rates. This study finds that, under these circumstances, the best age results are obtained when applying the refined dosimetric technique which combines the beta dose rate from NAA/DNC and gamma dose rate from Al2O3:C dosimetry.
Keywords: Optically Stimulated Luminescence; Woodland Archaeology; Aluminum Oxide Dosimeters; Ring Middens